2017
DOI: 10.1001/jamaophthalmol.2017.2838
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vision Loss With Cognition in Older Adults

Abstract: IMPORTANCE Visual dysfunction and poor cognition are highly prevalent among older adults; however, the relationship is not well defined.OBJECTIVE To evaluate the association of measured and self-reported visual impairment (VI) with cognition in older US adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
150
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(164 citation statements)
references
References 38 publications
10
150
2
2
Order By: Relevance
“…8 Reduced engagement in these cognitively stimulating activities may lead to brain reserve deficits, resulting in decline in cognitive function. [9][10][11][12][13] In this regard, several cross-sectional studies 12,[14][15][16][17] found a significant association between VI and decline in cognitive function. However, longitudinal reports [5][6][7]18 in this area are currently scarce and nonconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…8 Reduced engagement in these cognitively stimulating activities may lead to brain reserve deficits, resulting in decline in cognitive function. [9][10][11][12][13] In this regard, several cross-sectional studies 12,[14][15][16][17] found a significant association between VI and decline in cognitive function. However, longitudinal reports [5][6][7]18 in this area are currently scarce and nonconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is not a gold standard cut-off point for the CERAD, DSST and Animal Fluency test to identify low cognitive performance. Therefore, we used the 25th percentile of the score, the lowest quartile, as the cut-off point, which is consistent with methods used in the published literature [41]. Furthermore, considering that age has a significant effect on cognitive performance, the score was further categorized based on age (60 to < 70 years, 70 to < 80 years, and ≥ 80 years).…”
Section: Cognitive Performance Assessmentmentioning
confidence: 99%
“…Aging, Demographics and Memory Study (ADAMS) found evidence of an independent association between untreated poor vision and dementia. 19 Other epidemiological studies conducted in the United States, the Netherlands, Australia, and Mexico have also suggested an association between age-related eye conditions and cognitive decline, [20][21][22][23][24][25][26] but these studies have focused on cognitive decline rather than dementia, [22][23][24][25] had small sample sizes, 19 were not conducted in the United Kingdom, or analyzed only individuals aged 65 and older. [21][22][23][24][25] The current study cross-sectionally and longitudinally investigated whether self-rated impaired vision was independently associated with dementia in a representative sample of adults aged 50 and older in England.…”
mentioning
confidence: 99%